Does Getting Stigma Under the Skin Make It Thinner? Emotion Regulation as a Stress-Contingent Mediator of Stigma and Mental Health. (July 2018) - Burton, Charles L.; Wang, Katie; Pachankis, John E.
Emotion regulation deficits may link stigma to poor mental health, yet authors of existing studies have relied on self-reported stigma and have not considered contextual factors. In the present research, we examined associations among cultural stigma (i.e., objective devaluation of one's stigmatized status), emotion regulation deficits, and poor mental health. In Study 1, we created an index of cultural stigma by asking members of the general public and stigma experts to indicate desired social distance toward 93 stigmatized attributes. In Study 2, emotion regulation deficits mediated the association between cultural stigma and adverse mental health outcomes, including depressive symptoms and alcohol use problems, among individuals endorsing diverse stigmatized identities. The indirect effect of cultural stigma, via emotion regulation, on these outcomes was stronger among those reporting more life stress. These findings highlight the adverse impact of cultural stigma on mental health and its role in potentiating stigmatized individuals' susceptibility to general life stress.